A unique case of "double‐orifice aortic valve"—comprehensive assessment by 2‐, 3‐dimensional, and color Doppler echocardiography. Issue 9 (29th June 2016) - Stirrup, James E.; Cowburn, Peter J.; Pousios, Dimitrios; Ohri, Sunil K.; Shah, Benoy N.
Abstract : Transesophageal echocardiography (TEE) is a powerful imaging tool for the comprehensive assessment of valvular structure and function. TEE may be of added benefit when anatomy is difficult to delineate accurately by transthoracic echocardiography. In this article, we present 2‐, 3‐dimensional, and color Doppler TEE images from a male patient with aortic stenosis. A highly unusual and complex pattern of valvular calcification created a functionally "double‐orifice" valve. Such an abnormality may have implications for the accuracy of continuous‐wave Doppler echocardiography, which assumes a single orifice valve in native aortic valves.